The Effect of Leg Muscle Strength Training in Reducing Knee Pain Intensity among Elderly Women - Christiana, Metta; Muhaimin, Ahmad; Arif , Saifullah; Sumartiningsih, Sri (Media Ilmu Keolahragaan Indonesia, 2024)
Abstract. Aging naturally reduces physiology, increasing susceptibility to injuries, particularly in the knee joint, which supports substantial body weight and is vulnerable to osteoarthritis and ligament injuries. The current study investigates the effectiveness of leg muscle strength training in reducing knee pain intensity among elderly women aged 45 years and older residing in Gayamsari District, Semarang. A pre-experimental design employing a one-group pre-test post-test approach was implemented. Forty-two participants were selected using purposive sampling methods. The intervention involved leg muscle strengthening exercises conducted twice per week for six weeks, with each session lasting 40 minutes. Knee pain intensity was assessed using the Numerical Rating Scale both prior to and following the intervention. Data analysis was performed using the Wilcoxon signed ranks test due to non-normally distributed data. Findings indicated a statistically significant reduction in knee pain intensity, with average pre-test pain scores recorded at 3.2 ± 2.2 and average post-test scores recorded at 0.9 ± 1.4 (p = 0.000). Of the participants, 40 demonstrated a reduction in pain levels, whereas 2 participants showed no improvement, potentially influenced by additional medical conditions including gout and hypertension. In conclusion, leg muscle strength training significantly contributed to reducing knee pain intensity in elderly women, thereby justifying inclusion in rehabilitation programs targeting knee pain associated with osteoarthritis and ligament injuries. Further research is recommended to investigate tailored training protocols that account for co-morbid conditions and their impact on pain management efficacy. Abstract in Indonesia. Penuaan secara alami mengurangi fisiologi, meningkatkan kerentanan terhadap cedera, terutama pada sendi lutut, yang menopang berat tubuh yang substansial dan rentan terhadap osteoatritis dan cedera ligamen. Penelitian saat ini menyelidiki efektivitas latihan kekuatan otot kaki dalam mengurangi intensitas nyeri lutut di antara wanita lanjut usia berusia 45 tahun ke atas yang tinggal di Kecamatan Gayamsari, Semarang. Desain pra-eksperimental yang menggunakan pendekatan satu kelompok pra-tes pasca-tes diterapkan. Empat puluh dua peserta dipilih menggunakan metode purposive sampling. Intervensi melibatkan latihan penguatan otot kaki yang dilakukan dua kali seminggu selama enam minggu, dengan setiap sesi berlangsung selama 40 menit. Intensitas nyeri lutut dinilai menggunakan Numerical Rating Scale sebelum dan sesudah intervensi. Analisis data dilakukan dengan menggunakan uji peringkat bertanda Wilcoxon karena data tidak terdistribusi normal. Temuan menunjukkan pengurangan signifikan secara statistik dalam intensitas nyeri lutut, dengan skor nyeri pra-tes rata-rata tercatat sebesar 3,2 ± 2,2 dan skor pasca-tes rata-rata tercatat sebesar 0,9 ± 1,4 (p = 0,000). Dari peserta, 40 menunjukkan pengurangan tingkat nyeri, sedangkan 2 peserta tidak menunjukkan perbaikan, yang mungkin dipengaruhi oleh kondisi medis tambahan termasuk asam urat dan hipertensi. Sebagai kesimpulan, latihan kekuatan otot kaki berkontribusi signifikan terhadap pengurangan intensitas nyeri lutut pada wanita lanjut usia, sehingga membenarkan dimasukkannya dalam program rehabilitasi yang menargetkan nyeri lutut yang terkait dengan osteoatritis dan cedera ligamen. Penelitian lebih lanjut direkomendasikan untuk menyelidiki protokol pelatihan yang disesuaikan yang memperhitungkan kondisi komorbiditas dan dampaknya terhadap kemanjuran manajemen nyeri.